Leaf shedding and weather in tropical dry-seasonal forest shape the phenology of fungi – Lessons from two years of monthly surveys in southwestern Panama. (December 2015) - Piepenbring, Meike; Hofmann, Tina Antje; Miranda, Elvia; Cáceres, Orlando; Unterseher, Martin
Abstract: In the present study, conducted in a secondary dry-seasonal forest in the pacific lowlands of southwestern Panama over 2 years, fungal diversity is linked to plant phenology, litter, and climatic data. Agaricales fungi showed maximum species richness at the beginning of rainy seasons, probably due to the important litter accumulation during the dry season and the increase in humidity favoring fungal growth. Species richness declined during the wet season possibly due to torrential rains, moulds, and decreasing availability of nutrients. Occurrence of foliar pathogenic microfungi correlated negatively with flushing of new leaves at the beginning of the rainy season. Their incidence increased during the wet season and remained high during the dry season. Synchronization of leaf shedding in most tree species significantly reduced the yearly incidence of foliar pathogenic fungi causing an annual turn-over of fungal pathogens that probably contributes to maintain a high diversity of plant pathogenic species. Graphical abstract: Highlights: For the first time, seasonal dynamics of fungi is documented for a dry seasonal forest in the tropics over two years. Fruit bodies of Agaricales are mostly small, ephemeral, and mainly develop at the beginning of the rainy season. Foliar pathogenic microfungi are strongly affected by synchronized leaf shedding at the beginning of the rainy season. Annual turn-over of foliar pathogenic fungi probably contributes to maintain a high species diversity of pathogens.